Azure Virtual Desktop Specialist : exam study guide, AZ-140 - Darr, Shabaz (Apress, 2022)
Enhance your knowledge and become certified with the Azure Virtual Desktop technology. This book provides the theory, lab exercises, and knowledge checks you need to prepare for the AZ-140 exam. The book starts with an introduction to Azure Virtual Desktop and AZ-140 exam objectives. You will learn the architecture behind Azure Virtual Desktop, including compute, identity, and storage. And you will learn how to implement all of the services that make up the Azure Virtual Desktop platform. Each chapter includes exam and practice questions. The book takes you through the access and security of Azure Virtual Desktop along with its user environment and application. And it teaches you how to monitor and maintain an Azure Virtual Desktop infrastructure. After reading this book, you will be prepared to take the AZ-140 exam. What You Will Learn Plan an Azure Virtual Desktop architecture Install and configure apps on a session host Plan and implement business continuity and disaster recovery Understand user environment and applications in Azure Virtual Desktop Who This Book Is For Azure administrators who wish to increase their knowledge and become certified with the Azure Virtual Desktop technology.